Pengembangan Sistem Informasi Wisuda berbasis Web menggunakan Model MVC - Muhamad Idris; Amalia Rahmah (Jurnal Informatika Terpadu, 2022)
Using the website as an information system to support internal activities is one of the factors for the success and progress of educational institutions. One is using information systems to facilitate the academic community in registering for graduation. At STT Nurul Fikri, the registration process for graduation was still done manually and was too time-consuming. The purpose of this study was to design and build a website-based graduation registration information system (SIPUDA) using the Yii 2 framework. The method used in this research is a case study that collects data through interviews, observation, and documentation. The results of this study are a graduation registration information system that can help students register for graduation at STT Nurul Fikri whenever and wherever they are without having to take up a lot of time. However, a feature that has not been successfully created is the notification feature integrated directly with student emails.